FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PERAWAT - Faidiban, Ruth Harriet; Tatisina, Cut Mutia; Elmiyanti, Ni Ketut; Sari, Andi Nur Indah; Kariyadi, Kariyadi (Ensiklopedia of Journal, 2024)
Abstract: Work motivation is one of the factors that determine a person's performance. The size of the influence of motivation on a person's performance depends on how much motivation intensity is given. The results of a survey conducted by researchers in the operating room of Madani Hospital found that the number of active operating rooms was 7 operating rooms, the average operation per day was 15 patients, if one team had finished working the team seemed to be looking for excuses so they did not want to help other teams who still had patients. The purpose of the study was to determine the factors that influence nurse work motivation. This type of research is quantitative research with research design used cross sectioanal research design with a sample size of 35 nurses. The research was conducted at Madani Hospital. Data analysis used chi square test analysis. The results showed there was a relationship between tenure (p value: 0.031) and workload (p value: 0.022) on work motivation. It is recommended for hospital management to evaluate the performance, workload of health workers through internal meetings and build good organizational commitment in creating a conducive work ethic.Keywords: Workload, Motivation, Nurses